2021
DOI: 10.1021/acs.jafc.1c03307
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Plasma Membrane Malate Transporters Increased Lipid Accumulation in the Oleaginous Fungus Mucor circinelloides WJ11

Abstract: Malate as an important intermediate metabolite, its subcellular location, and concentration have a significant impact on fungal lipid metabolism. Previous studies showed that the mitochondrial malate transporter plays an important role in lipid accumulation in Mucor circinelloides by manipulating intracellular malate concentration. However, the role of plasma membrane malate transporters in oleaginous fungi remains unexplored. Therefore, in this work, two plasma membrane malate transporters "2oxoglutarate:mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Commercially proficient lipid production necessitates the development of recombinant strains that can accumulate elevated amounts of lipids, independent of the environmental fluctuations. So far, several genetic engineering techniques have been employed to boost lipid production via overexpression or the deletion of important genes and transporters such as malate and citrate transporters [ 39 , 40 , 41 , 42 , 43 ], AMP-activated protein kinase [ 44 , 45 ], the pentose phosphate pathway [ 18 , 46 , 47 ], Acyl CoA: Diacylglycerol Acyltransferase [ 48 ], lipases [ 49 , 50 , 51 ], malic enzymes [ 17 , 24 ], and the utilization of lignocellulosic biomasses [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commercially proficient lipid production necessitates the development of recombinant strains that can accumulate elevated amounts of lipids, independent of the environmental fluctuations. So far, several genetic engineering techniques have been employed to boost lipid production via overexpression or the deletion of important genes and transporters such as malate and citrate transporters [ 39 , 40 , 41 , 42 , 43 ], AMP-activated protein kinase [ 44 , 45 ], the pentose phosphate pathway [ 18 , 46 , 47 ], Acyl CoA: Diacylglycerol Acyltransferase [ 48 ], lipases [ 49 , 50 , 51 ], malic enzymes [ 17 , 24 ], and the utilization of lignocellulosic biomasses [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an important intermediate metabolite, malate, its subcellular location and concentration have significant effects on fungal lipid metabolism. Yang et al ( 149 ) deleted the two plasma membrane malate transporters “2-oxoglutarate:malate antiporter” (named SoDIT-a and SoDIT-b) of M. circinelloides WJ11 and analyzed their effects on growth ability, lipid accumulation and metabolism. Their results showed that the lipid content of the mutant was increased by ~10–40% compared to the control strain, indicating that defects in plasma membrane malate transport lead to an increase in malate for lipid synthesis.…”
Section: Metabolic Engineering Of Oleaginous Fungimentioning
confidence: 99%
“…It was found that in mt- overexpression and mt -knockout strains, fatty acid content was increased and decreased by 70% and 27%, respectively [ 70 ]. Moreover, knockout of plasma membrane malate transporters in WJ11 strain elevated the lipid content by 10–40% [ 71 ].…”
Section: Engineering Of Different Enzymes/genes/pathways To Enhance L...mentioning
confidence: 99%